Farming simulator modding with blender : a step-by-step guide to creating, optimizing and publishing mods - Gumster, Jason van (CRC Press / Taylor & Francis Group, 2025)
This is a comprehensive guide to creating and customizing mods for the popular video game Farming Simulator within Blender. This book covers all aspects needed to create your own vehicle mods from start to finish.The book begins with a basic introduction in Blender before showing you how to prepare your hierarchy and set up pivots. You’ll then learn to create physics components and how to set up your ModDesc and Vehicle XML files. The book then covers all you need to know about implementing vehicle functions before applying LOD meshes ahead of testing and finally publishing your mod on the official GIANTS ModHub.This book will appeal to all Farming Simulator modders, as well as those looking to learn game development concepts within Blender